Effect of slab charging temperature on reverse transformation behavior and induced crack sensitivity through experiments and micromechanical analysis. (September 2020) - Liu, Huasong; Lan, Peng; Dong, Yannan; Li, Shaoxiang; Tang, Haiyan; Zhang, Jiaquan
Abstract: The relationship between the popular hot charging associated surface crack sensitivity and the charging temperature was studied from the view of phase transformation. The austenite reversion with various charging temperatures was investigated through the thermal simulation experiments. And a two-dimensional representative volume element model was constructed to analyze the crack sensitivity related to microstructures. Compared to cold charging reversion, with the residual austenite in starting microstructure, the kinetics of hot charging reversion is slightly accelerated and the reversion behavior is changed. As the charging temperature increases, the austenite nucleation-growth from pearlite and ferrite grain boundaries are suppressed, while the austenitization through the growth of residual austenite is enhanced. The change of transformation behavior facilitates the formation of ferrite film during reversion through the morphological influence of austenitization modes. With the increasing of charging temperature, the film-like morphology of the evolved ferrite intensifies, especially in the two-phase temperature range. Consequently, the calculated crack sensitivity index rises sharply from 0.0006 to 0.029 when the charging temperature increases from A r 1 to A r 3 temperature, which is agreeable with the statistical production data. Additionally, it was observed that the incomplete γ  →  α  →  γ transformation cannot bring an effective austenite grain refining for the present steel. Graphical abstract: Unlabelled Image Highlights: The special behavior of reverse transformation from ferrite plus residual austenite structure was revealed and explained. The mechanism of forming film-like ferrite during hot charging reheating was proposed by the transformation behavior. The relations between slab charging temperature, reverse transformation behavior, and microstructure feature were constructed. The micromechanical simulation was applied to reveal the crack tendency in simulated hot charging reheating processes.